Pengaruh Neuro Linguistic Programming dengan Teknik Swish Pattern dan Circle of Excellence terhadap Intensi Merokok Siswa MTS X di Sleman - Doni Mahendra; Zahro Varisna Rohmadani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Nowadays, smoking is not only found among adults, even teenagers aged 11-14 years already have the intention to carry out smoking behavior, which makes the number of active smokers increase every year. Therefore, preventive efforts are needed to reduce the level of smoking intentions in adolescents before it leads to smoking behavior. One effort that can be made is to use the Neuro Linguistic Programming method with the Swish Pattern and Circle of Excellence techniques. The aim of this research is to find out whether there is an influence of Neuro Linguistic Programming with the Swish Pattern and Circle of Excellence techniques on smoking intentions. This research uses the type of research used in this research is quantitative research using quasi-experimental methods. The population used for this research was 90 class VIII students at MTs X in Sleman, aged 12-14 years, male. Then the research sample used a purposive sampling technique, totaling 20 students. This study used a smoking intention scale with a reliable value of 0.495. The research results were tested using the Paired Sample T-Test with a significance level (p) of 0.027 (p ˂ 0.05), meaning that there was a significant difference in smoking intentions between before and after treatment.